(untitled) (Revista CIATEC-UPF, 2020)
This work aimed the parametric study and cost optimization of reinforced concrete plane frames. To achieve these objectives, the total cost, composed by the costs of concrete, steel and formworks was minimized by the usage of a modified version of Harmony Search Algorithm. Cross sections dimensions, area of steel and concrete strength of beams and columns were taken as discrete design variables. The constraints related to dimensions and strength were based on the Brazilian standard ABNT NBR 6118 (2007). Some frame structures were analyzed in order to validate the formulation, as well the application of the optimization method. The results were compared to those obtained from the conventional design procedure, in an attempt to identify the influence of factors such as concrete strength, steel ratio and beams/columns costs on the optimal design of reinforced concrete building frames.